(untitled) (Fiep Bulletin - online, 2014)
In the last three proposed several decades they were elaborated seeking to improve the pedagogic practice of the physical education in the school ambit. This study aims at to verify the impacts of those proposals starting from the analysis of the work developed in that discipline in the schools of the Public and Private Net of the city of Pelotas and Rio Grande (RS). It is treated of studies of cases that use as instrument for collection of data observations, interviews, documental and bibliographical analysis. The study demonstrated that in the daily scholar of the physical education, the sport is the predominant content in the classes. Of the point of view of the corporal culture of movement, the “monoculture” of the sport is a limitation is tended as reference the group of possible experiences and considered fundamental for the student’s development. Besides, in the sport it is strongly present exclusion elements for being him/her inherent the seletividade through the competition and of the physical " revenue ". Above all, possibilities of other existences of the sphere playful are eliminated constituted by other human values. Like this, it is verified contradictions among what it is proposed in official documents, the scientific production of the area and the reality of the school physical education.